2001
DOI: 10.1001/archinte.161.13.1669
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Peak Expiratory Flow and the Development of Carotid Atherosclerotic Plaques

Abstract: Reduced lung function predicts the development of carotid atherosclerosis in elderly subjects. The nature of these associations remains largely unknown and merits further investigations. Nevertheless, assessment of lung function, which is simple and inexpensive, could help identify a population at high risk of atherosclerosis development and coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 46 publications
6
43
0
Order By: Relevance
“…Some previous studies [16][17][18][19] have demonstrated that airflow limitation with decreased predicted FEV 1 was associated with atherosclerosis. However, the atherosclerosis in the previous studies was assessed by carotid intima-media thickness and plaque.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Some previous studies [16][17][18][19] have demonstrated that airflow limitation with decreased predicted FEV 1 was associated with atherosclerosis. However, the atherosclerosis in the previous studies was assessed by carotid intima-media thickness and plaque.…”
Section: Discussionmentioning
confidence: 92%
“…11,12 Recent studies have demonstrated an association between COPD and cardiovascular disease, which accounts for approximately 25 to 50% of mortality. [13][14][15] Furthermore, recent studies [16][17][18][19] have demonstrated the association between pulmonary function and carotid atherosclerosis. These previous studies [16][17][18][19] assessed the atherosclerosis by measuring carotid intima-media thickness and plaques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, systemic inflammation may contribute to the diverse extrapulmonary comorbidities frequently seen in COPD patients, such as skeletal muscle wasting or cardiovascular disease [8,9], for which COPD is an independent risk factor [10]. Indeed, a leading cause of death in COPD includes cardiovascular disease, which is more frequent than respiratory failure in mild or moderate disease [11].…”
mentioning
confidence: 99%
“…Despite a tight coupling of cardiac and pulmonary systems to meet the organism's metabolic demand, the latter system has been largely excluded from investigation under this perspective. Epidemiological studies have, however, uncovered the independent role of impaired mechanical lung function as a prognostic factor for the development of arteriosclerosis, myocardial infarction, stroke, and complications in diabetes~Ebi- Kryston, 1988;Klein, Moss, Klein, & Cruickshanks, 2001;Truelsen, Prescott, Lange, Schnohr, & Boysen, 2001;Zureik, Kauffmann, Touboul, Courbon, & Ducimetiere, 2001!. Considerable effort has been devoted to the standardization of lung function testing~American Association for Respiratory Care @AARC#, 1994American Thoracic Society @ATS#, 1991; British Thoracic Society and the Association of Respiratory Technicians and Physiologists, 1994; European Respiratory Society @ERS#, 1993, 1997!. Furthermore, textbooks are available on the basics of lung function testing in pulmonary medicine~e.g., Forster, DuBois, Briscoe, & Fisher, 1986;Stocks, Sly, Tepper, & Morgan, 1996!.…”
mentioning
confidence: 99%